2017
DOI: 10.1051/matecconf/201711301013
|View full text |Cite
|
Sign up to set email alerts
|

Active element influence on the motor’s torque

Abstract: Abstract. The paper presents the numerical and experimental studies of the influence of the torque motor active element on the motor's torque. The tape active element is a novel type of a motor's stator organization, where the conventional winding is replaced by a tape winding. The force (torque) dependence over the rotor pole position using COMSOL is given; the tape winding resistance and the turns number are defined. The relative motor's characteristics are investigated and the maximum torque over the certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Besides, as shown previously [6][7][8], the magnetic flux density also depends on the pole pairs number of the magnetic system. Also in [6] it is indicated that for a given tape width the value of the double integral ) , , ( 0 I y x D remains practically constant when the pairs of poles number of the magnetic system changes.…”
Section: Resultssupporting
confidence: 55%
“…Besides, as shown previously [6][7][8], the magnetic flux density also depends on the pole pairs number of the magnetic system. Also in [6] it is indicated that for a given tape width the value of the double integral ) , , ( 0 I y x D remains practically constant when the pairs of poles number of the magnetic system changes.…”
Section: Resultssupporting
confidence: 55%